2021
DOI: 10.3390/agriculture11060554
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ruminal Fermentation Parameters and Altered Rumen Bacterial Community Composition by Formulated Rumen Buffer Agents Fed to Dairy Cows with a High-Concentrate Diet

Abstract: The effects of rumen buffer agents on ruminal fermentation parameters and bacterial community composition were determined using in vitro and in vivo experiments in three rumen-cannulated, high-concentrate fed Holstein Friesian dairy cows. Experiment 1 in vitro treatments included bentonite, calcium carbonate, calcium oxide, sodium bicarbonate, sodium sesquicarbonate, and processed coral, and unbuffered samples served as the control. Experiment 2 in vitro treatments were based on the formulation of various comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Removing H+ from the rumen ecosystem is known to increase ruminal pH and to stimulate ruminal microbial activity; thus, when CH 4 decreases, H+ may be used for producing SCFAs to ensure optimal ATP yield for the microbial mass production [2]. Increasing ruminal pH may increase protein solubility and generate branched-chain volatile fatty acids (BCVFA) production as isovalerate and isobutyrate [29]. Thus, it partly explains the increase in isobutyrate molar proportions consistent with high protozoal numbers and PF by MNM CETAB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Removing H+ from the rumen ecosystem is known to increase ruminal pH and to stimulate ruminal microbial activity; thus, when CH 4 decreases, H+ may be used for producing SCFAs to ensure optimal ATP yield for the microbial mass production [2]. Increasing ruminal pH may increase protein solubility and generate branched-chain volatile fatty acids (BCVFA) production as isovalerate and isobutyrate [29]. Thus, it partly explains the increase in isobutyrate molar proportions consistent with high protozoal numbers and PF by MNM CETAB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our previous study [ 3 ] showed that lactate production was higher in TMR containing IRGS than in hay-based TMR. In addition, the increase in the molar proportion of propionate might be attributed to the rumen microbes involved in the production of propionic acid, specifically, the Ruminococcus bromii [ 39 ]. The proportion of butyrate significantly increased in the L-IRGS TMR diet, apparently due to the changes in propionate concentration in TMR diets, whereas the acetate proportion remained constant throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcus Low relative abundance during heat stress is recognized due to its cellulose degradation functions (Correia Sales et al, 2021); specialized amylolytic bacteria responsible for cellulose degradation in the rumen (Ze et al, 2015;Ramos et al, 2021b); several species are capable of fermenting starch thus contributed to the higher abundance during high-concentrate diet period (Klieve et al, 2007;Ramos et al, 2021a) Ruminococcaceae bacterium sp.…”
Section: Ruminococcaceaementioning
confidence: 99%
“…Utilize soluble carbohydrates as an energy source (Zhao et al, 2019); more efficient in structural carbohydrates degradation (El-Kaoutari et al, 2013;Ramos et al, 2021a); relative abundance decreased during hot summer (Li et al, 2020) Flavobacteria Flavocateriaceae No data available yet.…”
Section: Bacteroidesmentioning
confidence: 99%